Water Consumption by Eucalyptus Hybrid - Dabral, B. G.; Raturi, A. S. (Indian Forester, 1985)
The paper presents the results of water comsumption by Eucaluptus hybrid trees during the last 27 months in 3m Ã— 3m Ã— 3m R.C.C. lyalmeter. Water consuption form 30 to 24.5 cm depth was slightly lower than the rainfall received, although water consuption from the entire soil depth(0-24.5) exceeded the rainfall due to the previously stored soil water. Maximum amount of waater was consumed during rains and the least during summer.